(untitled) (Polish Yearbook of International Law, 2022)
The issue of war reparations was a subject of controversy in Polish-German relations for a long time. This was due to the position of the Federal Republic of Germany that this issue had been deferred to the moment of German unifcation. The German concept of reparations also included the individual claims of Polish victims of National Socialism (Nazism). The case for interstate reparations from Germany to Poland was closed as a result of the Polish waiver of 1953, while the issue of individual compensation for Polish victims was symbolically resolved as a result of agreements between Poland and the Federal Republic of Germany only in 1990 and 2000. The scope and amount of any new payments depends on the agreements of particular countries or organizations with the Federal Republic of Germany. As long as the victims are still alive, new pragmatic solutions should not be ruled out.